Right ventricular-arterial coupling in severe tricuspid regurgitation: prognostic relevance of longitudinal strain. (4th February 2022) - Margonato, D; Ancona, F; Melillo, F; Ingallina, G; Stella, S; Biondi, F; Montorfano, M; De Bonis, M; Agricola, E
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND. Right ventricular-to-pulmonary artery (RV-PA) coupling integrates RV systolic function at a given afterload and has been shown to have a prognostic impact in different clinical settings. In the context of severe functional TR, it reflects RV adaptation to both volume and pressure overload. However, its prognostic relevance has not been extensively  examined in patients suffering from severe TR, and available data evaluated RV-PA coupling using the TAPSE/PASP ratio, with its intrinsic limitation especially in the setting of concomitant severe TR. In patients with severe TR, right ventricular free-wall longitudinal strain (RVFWLS) has been demonstrated to be more senstie in evaluation of subtle RV systolic dysfunction and to reclassify patients with impaired RV systolic function although conventional echocardiographic parameters within normal limits. PURPOSE.   To analyze whether the noninvasive evaluation of RV-PA coupling with the use of the RVFWLS/PASP ratio could improve risk stratification in patients with severe TR. METHODS. Baseline clinical and echcardiographic parameters and correlation with long-term outcome were assessed in 250 consecutive patients with severe TR referred at our center from December 2015 to December 2018. RESULTS. Patients were predominantly female, with severe cardiovascular risk factors and major comorbidities, history of heart failure (HF) and atrial fibrillation. RVFWLS/PASP ratio ≤ 0.32 (AUC 0.72, p < 0.001, sensitivity 70%, specificity 67%) marginally predicted the presence of baseline clinical RV HF (p = 0.05). After univariate and multivariate analyses, RV-PA coupling as assessed by RVFWLS/PASP ratio, but not by TAPSE/PASP, was independently associated with all-cause mortality (OR 0.007, p = 0.03) and, at follow-up, "RV-PA coupled patients", defined by RVFWLS/PASP ratio >0.26 (AUC 0.74, p < 0.001, sensitivity 77%, specificity 52%) showed higher surival rates (p = 0.02). CONCLUSIONS. RVFWLS/PASP ratio was systematically measured to possibly evaluate RV-PA coupling as a novel echocardiographic parameter in the context of patients with severe TR: it is independently associated with poor long-term prognosis and different values seem to improve irsk stratification in this cohort of patients.